A new concept in assessing adaptability index for superior potential cropping intensity in early-maturing rice - Anshori, Muhammad Fuad; Musa, Yunus; Farid, Muh; Jayadi, Muh; Bahrun, Abd Haris; Yassi, Amir; Sulaiman, Andi Amran; Huang, Yi Cheng; Casimero, Madonna; Llorca, Lizzida; Suwarno, Willy Bayuardi; Putra, Muh Mukhtadir; et al. (Frontiers Media, 2024)
Implementing a cropping intensity program with rice cultivation four times a year (CI 400) can be achieved using early maturing varieties of rice. However, this development needs to pay attention to the adaptability of the varieties planted to ensure successful implementation. The adaptability approach is a combination of assessing stability and productivity potential. This concept has been developed and applied in several studies, including research on rice. However, this approach is considered less comprehensive because it is non-parametric and only focuses on one stability analysis. Therefore, a systematic integration of various stability analyses, including index methods, is needed to comprehensively assess adaptability, particularly for early-maturing rice in South Sulawesi. This region is characterized by a dynamic climate zone and is one of the top four highest rice producers in Indonesia. Meanwhile, this study aims to develop a comprehensive adaptability index and select the best early-maturing rice varieties, especially in South Sulawesi. The investigation was conducted in Bone, Soppeng, and Gowa over two seasons using a nested randomized complete block design, with organized replications in each environment (location-season). Additionally, there was a significant focus on the application of five early-maturing and two check rice varieties, with each factor repeated three times at each location, totaling 126 experimental units. The results showed that the adaptability index, by combining stability rank accumulation with yield min max standardization, was effective at assessing the yield potential and stability of early-maturing rice varieties in supporting CI 400. Inpari 13 had the best index value at 0.55, followed by Cakrabuana at 0.31; hence both were recommended as adaptive early-maturing rice varieties, especially in South Sulawesi.